Limited protective effect of the CCR5Delta32/CCR5Delta32 genotype on human immunodeficiency virus infection incidence in a cohort of patients with hemophilia and selection for genotypic X4 virus. - Iversen, A; Christiansen, C; Attermann, J; Eugen-Olsen, J; Schulman, S; Berntorp, E; Ingerslev, J; Fugger, L; Scheibel, E; Tengborn, L; Gerstoft, J; Dickmeiss, E; et al. (2003)
The relationship among CCR5 genotype, cytomegalovirus infection, and disease progression and death was studied among 159 human immunodeficiency virus (HIV)-infected patients with hemophilia. One patient (0.6%) had the CCR5Delta32/CCR5Delta32 genotype (which occurs in approximately 2% of the Scandinavian population) and a rapid disease course. His HIV V3 region contained genotypic features attributable to X4 virus and resembled functionally verified X4 virus and virus from patients treated with a CD4 cell-stimulating drug, tucaresol. Age-related differences in disease progression rate and survival time were seen for CCR5/CCR5 patients. Surprisingly, no protective effect of the CCR5/CCR5Delta32 genotype on disease progression or survival was seen for children but was evident for adults. Age group-related immunologic differences might explain this variation, and transmission route and/or viral phenotype variation within donor virus may be related to the limited protection of the CCR5Delta32/CCR5Delta32 genotype. Sequence comparisons indicate that X4 virus can be selected in vivo due to either absence of CCR5 receptors or relative increase of CXCR4 receptors.